Optimization of conventional and ultrasound assisted extraction of flavonoids from grapefruit (Citrus paradisi L.) solid wastes. Issue 2 (December 2015) - Garcia-Castello, E.M.; Rodriguez-Lopez, A.D.; Mayor, L.; Ballesteros, R.; Conidi, C.; Cassano, A.
Abstract Flavonoid compounds from grapefruit wastes were obtained by conventional solid–liquid extraction (CE) and ultrasound assisted extraction (USE). Naringin was by far the most abundant flavonoid in the extracts ranging from 18 to 28 mg/g dw for CE and 24–36 mg/g dw for USE. Response surface methodology allowed obtaining predictive models for total phenolic content (TPC) and total antioxidant activity (TAA) as a function of the process variables ethanol concentration (EtC) (defined as weight of ethanol/weight of solution), temperature (T) and time (t) with reasonable success (CE-TPC, R2 = 0.86, CE-TAA, R2 = 0.85; USE-TPC, R2 = 0.82; USE, TAA, R2 = 0.86). USE was very effective when compared with conventional solvent extraction, allowing higher extraction yields (on average TPC 50% and TAA 66% higher) with lower temperatures and extraction times. Although the optimum process conditions indicate the use of a low ethanol concentration and ultrasounds (T = 25 °C, EtC = 0.4 (g/g) (40 g/100 g) and t = 55 min leading to TPC = 80.0 mg GAE/g dw and TAA = 38.3 mmol trolox/g dw), it has been proved that an USE treatment free of organic solvent (EtC = 0 g/g), at moderate temperature (25 °C) and short time (t = 3 min) leads to similar results (TPC = 75.3 mg GAE/g dw and TAA = 31.9 mmol trolox/g dw), suggesting its use for economic and environmental purposes.